Pengaruh Modal Sendiri dan KUR terhadap Pendapatan UMKM di Kecamatan Sindue - Ayuni, Ayuni; Munawarah, Munawarah; Kadang, Juliana; Fera, Fera (Penerbit Goodwood, 2025)
Purpose: This study seeks to investigate the impact of personal capital and People's Business Credit on the revenue of Micro, Small, and Medium Enterprises (MSMEs) in Sindue District, Donggala Regency. Methodology: The study employed a quantitative verification approach, focusing on grocery stall MSMEs in Sindue District. Using purposive sampling, 110 respondents were selected. Both primary and secondary data were analyzed through multiple linear regression. Results: The findings revealed that MSME revenue in Sindue District was significantly and positively influenced by Own Capital (52.4%) and People's Business Credit (39.8%), with both variables explaining 76.9% of the revenue variation. The remaining 23.1% was attributed to other factors not examined in this study. Conclusions: Own capital and KUR both significantly boost MSME income in Sindue District. Own capital offers flexibility, while KUR supports production. However, access barriers remain. Combining both funding sources is key to MSME growth. Limitations: This study focused solely on MSMEs in Sindue District. Future research should expand the sample size and include additional variables, such as pricing strategies and financial management, to provide deeper insights into factors affecting business income. Contribution: This study's findings are anticipated to assist the government and financial institutions enhance targeted financing policies and aid MSMEs in their financial decision-making.